The use of cultural identity in advertisements to strengthen the consumer-brand relationship.: Campaign “Tenemos Barrio, Tenemos Mundial” of Cristal beer. - Sheen Moreno, María José (2020)
Usually, in order to attract consumers and generate feelings of belonging, advertisements use the collective imagination that identifies a country or region to build an efficient message that links the values ​​of that culture with certain brands. In this regard, the advertising of alcoholic beverages has stood out for its constant creation of symbolic and experiential universes that allude to the place of origin of the product, in order to build identity narratives and motivate feelings of belonging in its consumers. It has been seen that the advertisements of Peruvian beer brands have not been immune to this trend, and have constantly resorted to cultural stereotypes materialized in advertisements that rest on a basis of significance aimed at building a perspective of cultural representation. The objective of this study has been to analyze, through focused interviews, how Peruvian university students interpret the cultural references shown in advertising spots as stimuli to encourage cultural identity. It has been possible to distinguish how in the participants of this research a close relationship is manifested between the recognition of cultural elements in advertising messages and subjective well-being. This phenomenon is modulated by various individual factors, specifically their need for belonging, which is formed from their social environment and adopts commercial messages as a conduit to their group ties.